RESEARCH ON KNOWLEDGE AND BEHAVIOR LEVEL IN SELF-MEDICATION OF GASTRITIS AMONG MEDICAL STUDENTS - Oi, San; Rizkifani, Shoma; Nurmainah, Nurmainah (Jurnal Mahasiswa Farmasi Fakultas Kedokteran UNTAN, 2019)
Self-medication is a process that is carried out to deal with complaints and minor ailments that are often experienced. Gastritis is a mild disease that can be self-medicated by individuals. The level of self-medicated knowledge among health students is in a good category. However, good knowledge does not always show good behavior in doing self-medication. The purpose of this study was to analyze the relationship between the level of knowledge and gastritis selfmedication behavior in health students. Methods : This type of study is an descriptive observational study with a cross-sectional study design. The sampling technique used was quota sampling. The data analysis used was the Spearman Rank correlation test with a confidence level of 95%. Results and Conclusions : Most respondents were 19 years old (34.769%), female gender (81.788%), third semester (34.438%). The most frequently consumed drug is PromagÂ® (62.914%), and the most often visited place to get an gastritis drug is a pharmacy (58.278%). The level of knowledge possessed by health students was classified as good, namely as many as 186 respondents (61.590%) and positive gastritis self-medication behavior as many as 229 respondents (75.828%).